The voice of clinical supervisors as a basis for developing a supervision model for nursing students in municipial health services. - Wannebo, Wenche; Bøgh Næss, Grethe; Eid, Hege Rasmussen (Nordisk Tidsskrift for Helseforskning, 2025)
High-quality supervision during clinical placements is essential for nursing students’ learning process. At the same time, the municipal healthcare service faces increasing challenges related to nurse recruitment, which may limit access to qualified practice supervisors. This highlights the need for sustainable supervision models that support student learning while being feasible within the time constraints of clinical practice. To explore which factors supervisors themselves consider critical for effective supervision and should be included in such a model, we conducted focus group interviews with experienced practice supervisors. The results showed that organizational factors, frameworks and resources, as well as relational aspects within the supervision context, play an important role.
Keywords: education; nursing; professional; sustainable